Quantitative trait loci and candidate gene analysis of citrus tristeza virus-citradia interaction - Asins, María J.; Bernet, Guillermo P.; Ruiz, C.; Cambra, Mariano; Puchades, Juan; Carbonell, Emilio A. (2017)
Citrus Tristeza Virus (CTV) has caused the death of millions of trees grafted on sour orange (C. aurantium). However, this rootstock is very well adapted to the Mediterranean, semi-arid conditions. A progeny of 104 citradias derived from the cross between C aurantium and Poncirus trifoliata was used to genetically analyse their interaction with CTV. The hybrids were grafted onto healthy sweet orange rootstocks. Three months later, each rootstock was graft inoculated with two patches of infected tissue (isolate T-346). CTV was detected by tissue blot immuno-assay in hybrids and infected patches for two to four years after inoculation. Additionally, CTV multiplication was evaluated every year as the optical density of double antibody sandwich enzyme-linked immuno sorbent assay reactions. A linkage map of P. trifoliata based on 63 markers, and another of C. aurantium based on 157 markers, were used. Most molecular markers were microsatellites and IRAPs. Some analogues of resistance and expressed sequences were also included for candidate gene analysis. Resistance against CTV was analysed as a quantitative trait (CTV accumulation) by QTL analysis to avoid the assumption of monogenic control. Three major resistance QTLs were detected where Ctv-R had been located previously in other progenies. Five minor QTLs were detected (Ctv-A(1) to Ctv-A(5)). Three significant epistatic interactions involving Ctv-R, and Ctv-A(1) were also found. An analogue of resistance is a candidate for Ctv-A(3) and two expressed sequences are candidates for Ctv-A(1) and Ctv-A(5).